(3GdCOhjI GdbdHjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI aUd Ef Gddg Ndb GdJLhja GdCjSQ ef JLhja GdbdH ddQhM heYfG dJhdOg hNdb GdQhM eWjI ddbhj GdfaSGfjI JSQj HgeG ai GdCZVGA s
(3BNQgG (B:s
(3agPG eG MVQfG ef GdcdGe ai GdCOhjI GdbdHjI s
(3Vef eLehY , JQJjHgG (B: 14s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs